Nox2 NADPH oxidase is dispensable for platelet activation or arterial thrombosis in mice - Sonkar, Vijay K.; Kumar, Rahul; Jensen, Melissa; Wagner, Brett A.; Sharathkumar, Anjali A.; Miller, Francis J.; Fasano, MaryBeth; Lentz, Steven R.; Buettner, Garry R.; Dayal, Sanjana (Blood advances, 2019)
Deficiency of the Nox2 (gp91phox) catalytic subunit of nicotinamide adenine dinucleotide phosphate (NADPH) oxidase is a genetic cause of X-linked chronic granulomatous disease, a condition in which patients are prone to infection resulting from the loss of oxidant production by neutrophils. Some studies have suggested a role for superoxide derived from Nox2 NADPH oxidase in platelet activation and thrombosis, but data are conflicting. Using a rigorous and comprehensive approach, we tested the hypothesis that genetic deficiency of Nox2 attenuates platelet activation and arterial thrombosis. Our study was designed to test the genotype differences within male and female mice. Using chloromethyl-dichlorodihydrofluorescein diacetate, a fluorescent dye, as well as high-performance liquid chromatography analysis with dihydroethidium as a probe to detect intracellular reactive oxygen species (ROS), we observed no genotype differences in ROS levels in platelets. Similarly, there were no genotype-dependent differences in levels of mitochondrial ROS. In addition, we did not observe any genotype-associated differences in platelet activation, adhesion, secretion, or aggregation in male or female mice. Platelets from chronic granulomatous disease patients exhibited similar adhesion and aggregation responses as platelets from healthy subjects. Susceptibility to carotid artery thrombosis in a photochemical injury model was similar in wild-type and Nox2-deficient male or female mice. Our findings indicate that Nox2 NADPH oxidase is not an essential source of platelet ROS or a mediator of platelet activation or arterial thrombosis in large vessels, such as the carotid artery. •Nox2 NADPH oxidase is dispensable for platelet ROS generation as well as platelet activation, adhesion, secretion, and aggregation.•Nox2 NADPH oxidase is not essential in mediating experimental thrombosis in major vessels, such as the carotid artery. [Display omitted]